2010
DOI: 10.1080/19479830903562041
|View full text |Cite
|
Sign up to set email alerts
|

Fusing high-resolution SAR and optical imagery for improved urban land cover study and classification

Abstract: The two objectives of this study are to compare the performances of different data fusion techniques for the enhancement of urban features and subsequently to improve urban land cover types classification using a refined Bayesian classification. For the data fusion, wavelet-based fusion, Brovey transform, Elhers fusion and principal component analysis are used and the results are compared. The refined Bayesian classification uses spatial thresholds defined from local knowledge and different features obtained t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 25 publications
(32 reference statements)
0
51
0
1
Order By: Relevance
“…However, the SAR results improved when the spatial resolution of the data increased (the resolution was 4 m, 3 m or 1.5 m). Many studies using automatic classification methods deal with satellite images with lower spatial resolutions (e.g., [26][27][28][29][30]), but high-resolution aerial or satellite data have also been used [24,31,32]. Generally, prior studies suggest that the combined use of both optical and SAR data is useful because of the complementary nature of these datasets.…”
Section: Comparison Of New Remotely Sensed Datasets For Land Cover CLmentioning
confidence: 99%
“…However, the SAR results improved when the spatial resolution of the data increased (the resolution was 4 m, 3 m or 1.5 m). Many studies using automatic classification methods deal with satellite images with lower spatial resolutions (e.g., [26][27][28][29][30]), but high-resolution aerial or satellite data have also been used [24,31,32]. Generally, prior studies suggest that the combined use of both optical and SAR data is useful because of the complementary nature of these datasets.…”
Section: Comparison Of New Remotely Sensed Datasets For Land Cover CLmentioning
confidence: 99%
“…At present, some progress has been made in this study area. In 1976, Ketting put forward the object-oriented method, and discussed one kind of segmentation algorithm ECHO [5] .Then, Benz, J. D. Watts, and Zhang Xiuying each elaborated the application of the method in their study, which get satisfactory classification results [6]. After 2008s, Ren Yuhuan provided available information for the detection of earthquake by using object-oriented method with Quick bird images [7].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the same system can be used in combination with higher resolution satellites such as RADARSAT-2 SAR, TerraSAR X and airborne SAR systems for monitoring land use. Amarsaikhan et al [17] and Brook et al [18] have also shown how the combined use of optical and SAR data sets can enhance urban feature detection and enhancement.…”
Section: Introductionmentioning
confidence: 99%